2021
DOI: 10.1017/s0007114521000829
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting with a high-protein diet mitigated osteoarthritis symptoms by increasing lean body mass and reducing inflammation in osteoarthritic rats with Alzheimer’s disease-like dementia

Abstract: Menopausal women are susceptible to osteoarthritis and memory impairment. We hypothesized that Alzheimer’s-like disease (AD) exacerbates osteoarthritis and that intermittent fasting(IMF) with a high-protein(H-P) diet would enhance memory function and relieve osteoarthritis symptoms in estrogen-deficient animals with surgically induced AD and osteoarthritis. The action mechanism was also explored. Ovariectomized Sprague-Dawley rats were fed high-fat(H-F) or H-P diets for two weeks, and then they had a hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…OA risk is affected by lifestyle, but few regimes efficiently prevent or reduce the it [ 31 ]. Fish oil, protein, dietary fiber, and polyphenols, including curcumin, are recommended to improve OA symptoms [ 32 , 33 , 34 , 35 ]. On the other hand, their efficacy is varied and controversial [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA risk is affected by lifestyle, but few regimes efficiently prevent or reduce the it [ 31 ]. Fish oil, protein, dietary fiber, and polyphenols, including curcumin, are recommended to improve OA symptoms [ 32 , 33 , 34 , 35 ]. On the other hand, their efficacy is varied and controversial [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…OA risk is closely related to obesity, and weight loss is recommended for reducing OA symptoms. Intermittent fasting is one weight-loss method and OA therapy [ 33 ]. The present study showed that PRS interacted with dietary intake, including energy, protein, fat, and alcohol, to influence OA risk, even though dietary intake did not affect OA risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, calorie restriction does not maintain or increase skeletal muscle mass, although it does maintain muscle strength [109]. Nevertheless, intermittent fasting has been reported to reduce fat mass and maintain or increase skeletal muscle mass by ameliorating oxidative stress and decreasing proinflammatory cytokines in human and animal studies [110][111][112][113]. Intermittent fasting reduces body fat mass, insulin resistance, and proinflammatory cytokines in adults; it also induces significant changes in gut microbiota communities, increases the production of short-chain fatty acids, and decreases the circulating levels of LPS in adults [110].…”
Section: Bcaa Effects On Metabolism and Sarcopenia Host Through The G...mentioning
confidence: 99%
“…After intermittent fasting, the relative abundances of Ruminococcus gnavus, Chitinophagaceae bacterium, Roseburia faecis, Paraburkholderia caribensis, Verrucomicrobiae bacterium Ellin516, Neisseria dentiae, and Streptococcus ferus increase [110]. Intermittent fasting modulates gut microbiota to increase Lactobacillales and decrease Clostridales in Alzheimer's disease-induced rats [111]. Therefore, intermittent fasting with a high protein diet may help maintain or increase skeletal muscle mass while modulating gut microbiota.…”
Section: Bcaa Effects On Metabolism and Sarcopenia Host Through The G...mentioning
confidence: 99%
“…As the normal control, male rats were given a sham-ORX operation by rubbing the testicles but not removing them. After the eighth week from the ORX or sham surgery, MIA (4 mg/50 µL saline; Sigma Co., St. Louis, MO, USA) was injected into the intra-articular cartilage through the patellar ligament of the left knee after anesthetizing them with intramuscular injections of a ketamine and xylazine mixture (100 and 10 mg, respectively) [15,16].…”
Section: Bilateral Orchiectomiesmentioning
confidence: 99%